Proceso de atención de enfermería en lactante de 11 meses con neumonía. - Vera Camacho, Joselyn Antonella (2020)
Nursing care issues are intensely significant instruments for the professional, which can facilitate patient care. In addition, they allow having a clear diagnosis and precise treatment to reduce the symptom picture that the infant presents using techniques and procedures, with the aim that the patient improves as soon as possible, this clinical case was carried out in an 11-month-old patient with a typical pneumonia diagnosis. Pneumonia is a contagion that occurs in the respiratory system because it mainly affects the lungs. This type of pathology can be transferred by immediate friction with individuals who are infected. Pneumonia is considered one of the pathologies with the highest mortality rates worldwide. Pneumonia if not treated in time can have complications such as leakage of the lung membrane, alveolar collapse, and the presence of air in the chest. The procedure to treat a lung infection is evaluated by the ages of the patients. In the case of lactating patients with infection, it is difficult to treat appropriately, so drugs such as amoxicillin are used and ampicillin, in more severe cases, cefuroxime is used. These pathologies can be prevented, with the correct washing of hands, preventing the patient from inhaling tobacco smoke, providing breast milk and having their vaccination complete. The 14 primordial deficiencies of the human that are described in Henderson's theory were used, in addition, the taxonomies of Nic, Noc and Nanda were used in this nursing patient, thus obtaining a faster diagnosis on the pathology of the patient and improving the symptom picture. Through a treatment carried out in this patient with pneumonia, a very favorable result was obtained, reducing respiratory distress, making the respiratory tract permeable, regulating his body temperature and vital signs.